Transient Detections and Other Real-Time Data Processing from MASTER-VWF Wide-Field Cameras. (22nd April 2010) - Gorbovskoy, Evgeny; Ivanov, Kirill; Lipunov, Vladimir; Kornilov, Victor; Belinski, Alexander; Shatskij, Nikolaj; Kuvshinov, Dmitry; Tyurina, Nataly; Balanutsa, Pavel; Chazov, Vadim; Kuznetsov, Artem; Kortunov, Petr; et al.
Abstract : Construction of robotic observatories has developed into an important and thriving field of astronomy. Their large field of view combined with the capability to be pointed at any direction makes robotic astronomical systems indispensable for tasks involving searches for transients like GRB, supernovae explosions, novae, and so forth, where both the time and direction of the search are impossible to predict. This paper describes prompt GRB observations made with MASTER-VWF wide-field cameras and the methods of image analysis and classification of transients used for real-time data processing. During seven months of operation six synchronous observations of gamma-ray bursts have been made using MASTER VWF facilities deployed in Kislovodsk and Irkutsk. In all cases high upper limits have been obtained.